القياس فى الحدود والكفارات : دراسة أصولية فقهية - حريز، عبدالمعز عبدالعزيز (جامعة آل البيت, 2007)
يتناول هذا البحث مسألة القياس في الحدود والكفارات عند الأصوليين، تحريرا وتحليلا وترجيحا، وركز الباحث في هذا الموضوع على تحرير محل النزاع والمسائل المتعلقة به لبيان المتفق عليه من المختلف فيه من المسائل وتبع هذا بيان لآراء العلماء وأدلتهم مع بيان أثر الاختلاف والراجح من الأقوال، وكان من أبرز نتائج هذه الدراسة أن محل النزاع إنما هو في إمكان إثبات أصل الحدود والكفارات بالقياس، وكان الراجح من الأقوال عند الباحث عدم جواز إثبات أصل الحدود أو الكفارات بالقياس. This research assesses and analyses the subject of the legitimacy of the analogical deduction in the cases related to al-Hudud and al-Kaffarat according to the scholars of the Science of Principles of Islamic Jurisprudence. The researcher has concentrated on clarifying the object of disagreement and the subtopics belonging to it. This is in order to shed light on the agreements and disagreements in the relevant subsidiary issues. All that is followed with a clarification for the different opinions of the scholars in this question, their evidence, the consequence of their dispute, and the selected one of their opinions to the researcher. However, one of the most important conclusions of this study is that; the object of controversy here relates to the possibility of validating passing the ruling of the ‘original case’ of al-Hudud or al-Kaffarat to the new applicable case by the analogical deduction. The researcher has come to a conclusion in this respect that the latter point is impermissible
606146
Keywords: الفقه الإسلامى -- أصول الفقه الإسلامى -- القياس -- الحدود -- الكفارات